Contagion Channels of the Subprime Financial Crisis to the NYSE Euronext European Markets using Copulas - Horta, P. J. B. (2012)
This paper tests whether there was contagion of the Subprime financial crisis to the European stock markets of the NYSE Euronext group (Belgium, France, the Netherlands and Portugal) and, if evidence of contagion is found, determines the transmission channel(s) through which the crisis was propagated. We date the beginning of the crisis as 1st August 2007 after the burst of the U.S. subprime bubble, ending on 7th December 2009 with the emergence of the Greek sovereign debt crisis. After assessing whether there is evidence of financial contagion in the stock markets, we examine whether the "wealth constraints" transmission mechanism prevails over the "portfolio rebalancing” mechanism. An additional test looks at the interaction between stock and bond markets during the crisis and allows us to determine if the transmission occurs due to the “cross market rebalancing” channel or to the “flying to quality” phenomenon. We use copula theory to model the dependence structure between the U.S. stock market and the other stock markets in the sample, during the pre-crisis and the turmoil period. The tests suggest that i) financial contagion is present in all analysed stock markets, ii) the "portfolio rebalancing" channel is the most important crisis transmission mechanism, iii) and the "flight to quality" phenomenon is also present in all analysed stock markets.